2021
DOI: 10.1038/s41388-021-01917-z
|View full text |Cite
|
Sign up to set email alerts
|

The newly identified MEK1 tyrosine phosphorylation target MACC1 is druggable by approved MEK1 inhibitors to restrict colorectal cancer metastasis

Abstract: Cancer metastasis causes >90% of cancer deaths and remains a major treatment challenge. Here we deciphered the impact of tyrosine phosphorylation of MACC1, a causative driver for cancer metastasis, for cancer cell signaling and novel interventions to restrict cancer metastasis. We identified MACC1 as new MEK1 substrate. MEK1 directly phosphorylates MACC1, leading to accelerated and increased ERK1 activation. Mutating in silico predicted hierarchical MACC1 tyrosine phosphorylation sites abrogates MACC1-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…MACC1 has proven to be a prognostic marker that is predictive of therapy response and targetable by various drugs [ 4 , 5 , 26 , 27 ]. Two important effects associated with increased MACC1 expression are increased cell migration and proliferation [ 4 , 5 ], both being hallmarks of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MACC1 has proven to be a prognostic marker that is predictive of therapy response and targetable by various drugs [ 4 , 5 , 26 , 27 ]. Two important effects associated with increased MACC1 expression are increased cell migration and proliferation [ 4 , 5 ], both being hallmarks of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Both the HGF/c-Met axis and PI3K are strongly involved in cytoskeletal reorganization and regulation of cell migration [ 33 , 34 , 35 ]. Consequently, MACC1 was demonstrated to induce increased cell migration [ 4 , 26 , 29 , 36 , 37 , 38 , 39 , 40 ]. Based on these studies, we expected an MACC1-induced increase in single cell and/or collective migration, yet we could verify this only for collective migration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that MEK1 directly phosphorylates MACC1, leading to activation of MACC1-induced migration and metastasis in colorectal cancer [ 19 ]. In a next step, we were able to show that the inhibition of MEK1, either by RNAi or by the approved MEK1 inhibitor selumetinib, leads to a reduction in MACC1-induced effects in vitro and in vivo [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…We could show by in silico and functional analyses that MACC1 is post-translationally activated by phosphorylation attained by mitogen-activated protein kinase 1 (MAP2K1, MEK1). The MACC1-induced biological and phenotypical effects were reduced in vitro and in vivo by using the MEK1-inhibitor selumetinib (AZD6244) in colorectal cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…MACC1, an oncogene on human chromosome 7p21.1, is an important premetastasis factor of human colon cancer. In recent years, more and more pieces of evidence have demonstrated that MACC1 plays a role in the occurrence and progression of tumors [7,8]. MACC1 has been found to be less expressed in normal tissues but more overexpressed in colon, gastric, lung, esophageal, and other peritoneal tumor tissues [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%